2019
DOI: 10.26905/jkdp.v23i3.3228
|View full text |Cite
|
Sign up to set email alerts
|

Strategic Management Accounting disclosure, ownership structure, and firm characteristics in Indonesia manufacturing companies

Abstract: Why managers should choose to disclose their information with investors is one of the major issues in accounting research. Because of information asymmetry and the agency problem, disclosure is an important aspect of the modern capital market. This study aims to measure the extent of Strategic Management Accounting (SMA) disclosure and the impact of ownership structure (managerial ownership, foreign ownership, government ownership) and firm characteristics (firm size, leverage, profitability) on SMA practices … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
3
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 53 publications
(100 reference statements)
0
5
3
2
Order By: Relevance
“…The findings of this study are consistent with previous research that has shown a positive relationship between block ownership and disclosure of strategic management accounting information (e.g., Wang & Zang, 2009). Moreso, this study's results of a negative non-substantial effect of the current year's block ownership on SMAID partly disagree with the work of Honggowati et al (2019), who found a positive relation with SMAID. The apparent dichotomy is, however, contextual since this current study was conducted in Ghana (Africa) and that of Honggowati et al (2019) was done in Indonesia (Asia).…”
Section: Effect Of Block Ownership On Smaidcontrasting
confidence: 99%
See 1 more Smart Citation
“…The findings of this study are consistent with previous research that has shown a positive relationship between block ownership and disclosure of strategic management accounting information (e.g., Wang & Zang, 2009). Moreso, this study's results of a negative non-substantial effect of the current year's block ownership on SMAID partly disagree with the work of Honggowati et al (2019), who found a positive relation with SMAID. The apparent dichotomy is, however, contextual since this current study was conducted in Ghana (Africa) and that of Honggowati et al (2019) was done in Indonesia (Asia).…”
Section: Effect Of Block Ownership On Smaidcontrasting
confidence: 99%
“…Moreso, this study's results of a negative non-substantial effect of the current year's block ownership on SMAID partly disagree with the work of Honggowati et al (2019), who found a positive relation with SMAID. The apparent dichotomy is, however, contextual since this current study was conducted in Ghana (Africa) and that of Honggowati et al (2019) was done in Indonesia (Asia).…”
Section: Effect Of Block Ownership On Smaidcontrasting
confidence: 99%
“…The application of SMA has a positive impact both financially and non-financially. Honggowati et. al.…”
Section: Strategic Management Accountingmentioning
confidence: 99%
“…The usage of this SMA provides both financial and non-financial benefits. (Honggowati et al, 2019) research shows how the firm's ownership structure, business size, and profitability will all be positively and significantly impacted by the disclosure of SMA. Companies that use management accounting practices perform better than those that do not apply them.…”
Section: Introductionmentioning
confidence: 99%